2013
DOI: 10.1103/physreve.87.044201
|View full text |Cite
|
Sign up to set email alerts
|

Granular convection and the Brazil nut effect in reduced gravity

Abstract: We present laboratory experiments of a vertically vibrated granular medium consisting of 1-mm-diameter glass beads with embedded 8-mm-diameter intruder glass beads. The experiments were performed in the laboratory as well as in a parabolic flight under reduced-gravity conditions (on Martian and Lunar gravity levels). We measured the mean rise velocity of the large glass beads and present its dependence on the fill height of the sample containers, the excitation acceleration, and the ambient gravity level. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…Using an experimentally obtained scaling relation, they found that the convective velocity is scaled by g 0.97 . While the intruder's rise velocity (BNE rate) and convective velocity are different quantities, Yamada and Katsuragi (2014) is roughly consistent with Güttler et al (2013). However, the reason of difference between Güttler et al (2013) and Matsumura et al (2014) remains unclear.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Using an experimentally obtained scaling relation, they found that the convective velocity is scaled by g 0.97 . While the intruder's rise velocity (BNE rate) and convective velocity are different quantities, Yamada and Katsuragi (2014) is roughly consistent with Güttler et al (2013). However, the reason of difference between Güttler et al (2013) and Matsumura et al (2014) remains unclear.…”
Section: Introductionmentioning
confidence: 88%
“…While the intruder's rise velocity (BNE rate) and convective velocity are different quantities, Yamada and Katsuragi (2014) is roughly consistent with Güttler et al (2013). However, the reason of difference between Güttler et al (2013) and Matsumura et al (2014) remains unclear. In any case, all these experimental and numerical results suggest that the granular convection can occur with very low velocity even under the microgravity condition.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, the vibration induced convection in the container creates a wide upward flow in the central part of the system but only a thin downward flow along its boundaries so that all sorts of grains can rise to the surface but only small particles can dive back to the bottom. Investigations during parabolic flights (Güttler et al 2013) have shown that BNE can be observed in low gravity conditions even though its driving mechanisms are strongly linked to gravity, although sometimes in a complex manner (Staron 2016). This result consolidates the theory that certain surface structures on asteroids are created by this kind of segregation (Miyamoto et al 2007).…”
Section: Segregationmentioning
confidence: 99%